1997
DOI: 10.1046/j.1526-4610.1997.3705296.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihistamine Responsive Cluster Headache in a Teenaged Girl

Abstract: Episodic cluster headache is a well-recognized entity usually starting in the second decade of life. Uncommonly, the first typical symptoms may present in the first decade of life, but are rarely recognized as such during childhood. We report a 12-year-old girl who presented with a 1-year history of bouts of right-sided hemicrania with ipsilateral, clearly demarcated, redness and itching of the skin of the face, lasting from 15 minutes to 2 hours per day. The episodes recurred up to several times daily for a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
1
10
0
4
Order By: Relevance
“…Previous authors1 2have suggested that, although symptoms may begin in childhood, the diagnosis often goes unrecognised.…”
mentioning
confidence: 99%
“…Previous authors1 2have suggested that, although symptoms may begin in childhood, the diagnosis often goes unrecognised.…”
mentioning
confidence: 99%
“…No controlled study has been reported. Interestingly, a study in which a 12-year-old female was treated with antihistamine prophylaxis, first with astemizole and then with loratadine for 2 years, demonstrated this regimen to be effective [8]. Our case underwent also consecutive trials of, antihistamine prophylaxis (cyproheptadine hydrochloride 4 mg/day), flunarizine (5 mg/day), verapamil (80 mg/day), without efficacy.…”
Section: Discussionmentioning
confidence: 83%
“…According to these data, the most effective symptomatic treatments are oxygen [7982], sumatriptan [81, 83] and acetylsalicylic acid [8084]. Prophylactic treatments reported in literature are prednisone/prednisolone [85, 86], indomethacin [84], pizotifen [81], verapamil [81, 82, 87], methysergide [79, 83, 85], loratadine [88], astemizole [88] and flunarizine [89]. No controlled study has been reported.…”
Section: Management Of Headachesmentioning
confidence: 99%